Love in the Spotlight : The Nature of Love - Book 3 - Shiloh, Toni (Thorndike, Maine : Center Point Large Print, 2025)
"Dr. Erykah Kennedy, a renowned orthopedic surgeon, finds herself at a crossroads in life. At forty, shes achieved remarkable success in her career, yet when it comes to her love life, she feels fractured. But when she meets Christian Gamble, a passionate wildlife conservationist, an unexpected bond forms between them despite their contrasting worlds. Chris has yet to find someone to share his adventures with, but as his friendship with Erykah blossoms, he begins falling for her in every way. When tragedy strikes and Erykah suddenly becomes guardian to her nieces, Chris helps her pick up the pieces. With their lives turned upside down, finding their way to a lasting love while putting their faith in God may be the biggest challenge theyve ever faced."--
Keywords: Middle-aged women -- Fiction; Life change events -- Fiction; Man-woman relationships -- Fiction; Women surgeons -- Fiction; Wildlife conservationists -- Fiction; African Americans -- Fiction; Colorado -- Fiction; Christian fiction; Romance fiction; Large print books